The Shift of Al-Shawkani's Theological Thinking in Tafseer Fath al-Qadeer from Zaydi Shi’i to Ash’ari Sunni - Atabik, Ahmad (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2020)
This article aims to examine Al-Shawkani's theological thinking in Tafseer Fath al-Qadeer, which allegedly underwent a shift from the Zaydi (Fivers) Shi'i sect to Ash'ari (Twelver) Sunni theology. Tafseer Fath al-Qadeer is Al-Shawkani's masterpiece in the field of commentary. Al-Shawkani was a leading scholar in Yemen from the late medieval period to the modern era. He grew up in the Zaydi Madhab (school of thought). Nevertheless, he contradicted his original madhab, leading to a shift in his theological thinking. This study employs a qualitative approach using textual analysis of Tafseer Fath al-Qadeer to explore Al-Shawkani's theological perspectives and the reasons underlying this shift. Al-Shawkani's shift in thought becomes evident in his commentary on theological verses in Tafseer Fath al-Qadeer. Referring to Al-Shawkani's arguments on theology, such as issues on seeing God in the hereafter, the coming of God, martyrdom, and istiwa' (God's residence), Al-Shawkani leaned more toward the arguments proposed by the Ash'ari school rather than those by the Zaydi or Mu'tazili madhab. The findings reveal that Al-Shawkani frequently criticized Mu'tazili thoughts using both naqli (scriptural) and aqli (reasoning) propositions, signaling a departure from Zaydi theology. However, in the debate about the Quran's position—whether it is qadim (eternal) or created— Al-Shawkani maintained an independent stance. This shift in thought is reasonable, considering that Al-Shawkani, as a moderate Zaydi Shiite, sought to open himself to theological perspectives from other madhabs, which he considered more accurate. This research contributes to the scholarly understanding of theological evolution within Islamic traditions by demonstrating Al-Shawkani's methodological approach to reconciling theological divergence. It also provides a framework for examining inter-sectarian influences in Islamic theology and their impact on exegetical works.